Genetic Determinants of Plasma Factor VII Activity in the Japanese - Kario, Kazuomi; Narita, Naoko; Matsuo, Takefumi; Kayaba, Kazunori; Tsutsumi, Akisumi; Matsuo, Masafumi; Miyata, Toshiyuki; Shimada, Kazuyuki (Thrombosis and Haemostasis, 1995)
We investigated the frequency of the factor VII Gln353 (FVII Gln353) allele in Japan, where coronary artery disease is much less common and factor VII coagulant activity (FVIIc) is lower than in Western countries. Japanese males (n = 144) aged 40-59 years living in 2 different districts were studied, and the FVIIc and activated factor VII (FVIIa) levels were measured with human (FVIIa Hum) and bovine soluble tissue factor (FVIIa Bov). The frequency of the FVII Gln353 allele in the 2 districts was 0.026 and 0.052 (combined: 0.034), which was about one third of that in a European population. Thus, the lower FVIIc level in Japanese is not due to the effect of FVII Gln353 allele. Ten individuals with the Gln353 allele showed a 39% decrease of FVIIa Hum levels and a 29 % decrease of the FVIIa Bov level compared with 134 individuals homozygous for the FVII Arg353 allele. These decreases of FVIIa were greater than the decrease of FVIIc (17%), suggesting that FVII Gln353 may be difficult to activate in vivo. The marked decrease of FVIIa levels in individuals with the FVII Gln353 allele suggests that they are genetically protected against cardiovascular disease irrespective of ethnic background, by virtue of their decreased FVIIa level.